SYSTEMATIC LITERATURE REVIEW : FAKTOR DAN DAMPAK KECEMASAN MATEMATIS MAHASISWA PENDIDIKAN MATEMATIKA DAN CALON GURU PADA PRAKTIK MENGAJAR - Latifah, Murniati Nur; Pujiastuti, Heni; Mustafa, Ade Nandang (De Fermat : Jurnal Pendidikan Matematika, 2026)
This systematic literature review aims to identify and synthesize literature on the causes, impacts, and solutions to mathematics anxiety in mathematics education students or prospective mathematics teachers during teaching practice. The literature search was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol through the Google Scholar and Garuda databases with a publication year range of 2016 - 2026. A total of 85 articles were found in the identification stage. Through the PRISMA screening stages, 4 articles that met the inclusion criteria were obtained to be analyzed in-depth using qualitative narrative synthesis.. The findings indicate that the causes of anxiety are dominated by lack of material preparation, low self-confidence, and students’ fear of being unable to answer questions or interact with students. The impact is reflected in the cognitive aspects (loss of focus or blank) and somatic aspects (heart palpitations), which lead to passive teaching styles, hesitation, and minimal interaction among students. The conclusion of this study emphasizes the urgency of evaluating the learning program for prospective teacher students so that it not only emphasizes mastery of material and pedagogy, but also includes psychological development, emotional regulation, and the creation of a constructive learning environment to build self-confidence as prospective educators.